PENGARUH SERVANT LEADERSHIP DAN KOMPETENSI PEDAGOGIK TERHADAP KINERJA GURU DENGAN MEDIASI MOTIVASI KERJA - Sry Meylaningsih; Maman Suryaman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the influence of servant leadership and pedagogical competence on teacher performance with work motivation as a mediating variable. The research employed a quantitative approach with a survey method involving teachers at SMA YP IPPPI Petojo as respondents. Data were collected using a Likert-scale questionnaire and analyzed through path analysis using SmartPLS version 4. The results indicate that servant leadership has a positive and significant effect on both work motivation and teacher performance. Pedagogical competence also positively influences work motivation and teacher performance. Furthermore, work motivation partially mediates the relationship between servant leadership and pedagogical competence on teacher performance. This finding implies that teacher performance improvement is not solely determined by leadership and pedagogical abilities but also by the level of work motivation among teachers. The study suggests that school principals should apply the principles of servant leadership that emphasize empowerment and teacher well-being while simultaneously strengthening pedagogical competence through continuous professional development. Such efforts can foster higher work motivation and lead to sustainable improvement in teacher performance.